2015
DOI: 10.1097/jom.0000000000000539
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Body Mass Index and Health and Economic Outcomes in the United States

Abstract: Increasing BMI was associated with decreasing health status and increasing work-related impairment, healthcare resource utilization, and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
6
19
0
2
Order By: Relevance
“…Consistent with our results, other studies have found that obesity has economic consequences;[2] on the one hand, it causes unemployment[2627] or discrimination in employment and wages,[28] reduces the income,[1129] reduces productivity,[230] leads to earlier retirement[25] and employees face more healthcare costs. [11] The important thing is that obese people will not be able to work efficiently due to problems and disabilities, and by decreasing their economic life and early employment, the whole economic system of the country will be endangered.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our results, other studies have found that obesity has economic consequences;[2] on the one hand, it causes unemployment[2627] or discrimination in employment and wages,[28] reduces the income,[1129] reduces productivity,[230] leads to earlier retirement[25] and employees face more healthcare costs. [11] The important thing is that obese people will not be able to work efficiently due to problems and disabilities, and by decreasing their economic life and early employment, the whole economic system of the country will be endangered.…”
Section: Discussionsupporting
confidence: 91%
“…The economic burden of T2D is increased in patients who are overweight or obese 10 . These patients are at increased risk of co-morbidities and, consequently, have significantly greater medical expenditures than individuals with diabetes and normal weight [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…The current study contributes information on precisely these measures. DiBonaventura et al [34] conducted a study in which they identified an association between increased BMI and decreased work productivity, indicating that public expenses and personal income might also be affected by obesity. Our findings support this consideration and draw attention to the significant impact of obesity on the individuals' personal life with regard to income, in addition to its negative impact on socioeconomics.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the increasing prevalence of obesity and its potential impact on society, it is important to provide information on direct healthcare costs and other obesity-related costs of socioeconomic importance as well. DiBonaventura et al [34] found a decrease in work productivity with increasing BMI. They found that health problems among obese individuals resulted in an overall work impairment of 20%.…”
Section: Introductionmentioning
confidence: 99%